Tinjauan Model Pembelajaran Blended Learning pada Perguruan Tinggi di Era New Normal Covid-19: Kebijakan dan Implementasi - Zamzami Zainuddin (Asia-Pacific Journal of Public Policy, 2021)
This article aims to review the potential of a Blended learning model implementation in Indonesian higher education institutions during the time of Covid-19. This conceptual paper attempts to explain the concept of Blended learning in terms of theory and practice, based on the literature discussed in several reputable international journals. Blended learning is defined as a learning model integrating face-to-face instruction with an online learning environment or e-learning. Initially, this model proposes to improve the deficiencies of a traditional learning model which is lack of technological resources, and at the same time to develop the gap of e-learning practice which is lack of a face-to-face learning experience. In the blended instruction, students will learn through face-to-face interaction in the classroom and supported by digital media such as a Website, Video, or Learning Management System (LMS). Meanwhile, the use of technologies is ordinarily applied for students' learning and peer-interaction outside of the class, especially for online discussion and homework submission. This method emphasizes that learning activity should not only occur in the classroom but also outside of the class through the digital device.